Role of Servant Leadership, Talent Management, Knowledge Management and employee performance - Sumarsi, Sumarsi (International Journal of Social and Management Studies, 2020)
The purpose of this study is to explain the partial or simultaneous influence on the variables of servant leadership, talent management, knowledge management and employee performance. The sample in this study amounted to 560 respondents with a questionnaire tool using purposive sampling technique. This study uses a quantitative approach with descriptive and associative research techniques. The results of this study indicate that there is a significant influence partially and simultaneously on the variables of servant leadership, talent management, knowledge management and employee performance. From the results of this study, the variable that has the greatest influence is knowledge management.